Mutation of conserved MHC class I cytoplasmic tyrosine affects CD8+ T cell priming, effector function, and memory response - Sun, Yimo; Tang, Yitao; Ortiz, Priscilla; Nassif Rausseo, Barbara; Pazdrak, Barbara; Elzohary, Lama; Katailiha, Arjun; Talukder, Amjad; Yee, Cassian; Davis, Richard Eric; Lizée, Gregory (Frontiers in Immunology, 2025)
The cytoplasmic domain of MHC class I (MHC-I) molecules contains a single, highly conserved tyrosine residue (Y320). In previous work, we found that mice expressing a Y320F-mutated form of H-2Kb had reduced capacity to generate Kb-restricted cytotoxic T lymphocyte (CTL) responses following viral infection, due at least in part to defects in endolysosomal trafficking of H-2Kb and antigen cross-presentation by dendritic cells (DCs). In this study, we investigated whether there are additional, post-presentation dependencies on Y320 for T cell priming. We engineered both human- and mouse-derived antigen-presenting cells (APCs) to express either wild-type MHC-I or variants of MHC-I containing Y320F or Y320E mutations. We found that Y320E-mutated HLA-A*0201 elicited enhanced in vitro priming and expansion of human antigen-specific CD8+ T cells, which showed a unique transcriptional profile compared to T cells primed with APCs expressing either WT or Y320F-mutated A*0201. Furthermore, the Y320E variant of H-2Kb expressed in the context of a murine DC vaccine model induced altered T cell differentiation kinetics while improving both anti-tumor immunity and augmenting the magnitude of memory CD8+ T cell responses in vivo. These results suggest that Y320 phosphorylation of MHC-I may play a role in determining the fate and function of CD8+ T cells and suggest a novel strategy for improving DC-based cancer immunotherapies.